APPLICATION OF PERFORMANCE ASSESSMENT WITH METHOD DIFFICULTY LEVEL, DISTINGUISHING POWER, DISTRACTOR EFFECTIVENESS, AND ANOVA (Case Study: Paper Based Test (PBT) Period 2 Questions 2020–2021 Islamic University of Indonesia) - Khoirunnisa, Safira; Widodo, Edi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The quality of human resources can be improved through education. The Islamic University of Indonesia provides various selection patterns for prospective new students, one of which is PBT. Questions in PBT need to be analyzed to get quality students. The length of time to analyze the performance of questions that include the level of difficulty, distinguishing power, and distractor effectiveness in PBT Period 2 2020-2021 UII is one of the reasons for making computer programs using Microsoft Excel 2013. The methods used are simple random sampling and One-Way ANOVA analysis. The results of this study can make it easier to process data and analyze the performance of the questions with the help of the OASIS application which can be used as material for future evaluation. Analysis of the performance of the questions is classified as very difficult and difficult at the level of difficulty, the category is bad on the distinguishing power, and the effectiveness of the distractor is functioning properly, and there is one of the scores obtained by the test takers from three types of questions with the choice of the Faculty of Medicine and not choosing the Faculty of Medicine of UII which has the average is different from the others.